Delaying Broccoli Floret Yellowing by Phytosulfokine α Application During Cold Storage - Aghdam, Morteza Soleimani; Alikhani-Koupaei, Majid; Khademian, Raheleh (Frontiers in Nutrition, 2021)
Herein, we investigated the mechanism by which phytosulfokine α (PSKα) at 150 nM delays floret yellowing in broccoli during storage at 4 °C for 28 days. A higher endogenous accumulation of hydrogen sulfide (H2S) resulting from a higher gene expression and activities of L-cysteine desulfhydrase (LCD) and D-cysteine desulfhydrase (DCD) in broccoli floret treated with 150 nM PSKα may serve as an endogenous signaling molecule for delaying senescence. Also, the suppressed ethylene biosynthesis in broccoli florets treated with 150 nM PSKα might be ascribed to lower gene expression and activities of ACC synthase (ACS) and ACC oxidase (ACO). Furthermore, lower gene expression and activities of Mg2+ dechelatase (MDC), pheophytinase (PPH), and pheophorbide a oxygenase (PaO) might be the reasons for the higher accumulation of chlorophyll in broccoli florets treated with 150 nM PSKα. Based on our findings, the exogenous application of PSKα could be promising for delaying senescence in broccoli florets.